Investigating the effect of strategic planning on human performance from the perspective of the staff of Shohada Tajrish Hospital in Tehran - Samane Davoodabadi; Mohammad hassan Ahmadpour; Amirashkan Nasiripour; Hossein Shahnavazi (Tehran University of Medical Sciences, 2021)
Introduction:The purpose of this study is Investigating the effect of strategic planning on human performance from the perspective of the staff of Shohada Tajrish Hospital in Tehran. Materials and Methods: This research is applied-practical in terms of purpose and correlational in terms of nature and descriptive method. The statistical population of the present study includes all permanent staff of Shohada Tajrish Hospital. Using simple random sampling method and according to Cochran's formula, 184 people were selected as a statistical sample. In this study, the Strategic Human Resources Management Questionnaire and the Performance Questionnaire were used to collect data. Experts' opinions were used to confirm the validity of the questionnaire and SPSS software was used to assess the reliability. Cronbach's alpha was 0.868 and 0.751. SPSS software and simple linear regression were used to analyze the data. Results: The results showed that planning, supply, development, performance management, reward and employee relations have a significant effect on the performance of employees of Shohada Tajrish Hospital in Tehran. Conclusion: Since the results of the research indicate a very strong relationship between strategic human resource management and the performance of the organization in Shohada Tajrish Hospital, it is necessary to pay sufficient attention to human resource management in health centers. It is also necessary to pay special attention to categories such as human education and development, effective interaction and communication with employees, and hiring and hiring.